O controle externo de licitações exercido pelo Tribunal de Contas da União à luz da Lei nº 8.666/1993 e Lei nº 14.133/2021 - Teixeira, Fernando Julio (2023)
This monographic work aims to investigate the central aspects of the scope of the exercise of the constitutional attribution conferred to the Federal Court of Accounts, with regard to the external control of administrative activity, especially related to public bids in the light of Law nº 8.666/1993 (former, however, the bidding and contract law is still in effect) and Law No. 14.133/2021 (new bidding and contract law also in force), since its inception, with the initiation of an internal administrative process, pervading the external phases of bidding procedures and the incidence of control and its consequences, both from the Public Administration perspective, as well as from the individual interested in contracting with the Public Power. To this end, it will be essential to understand the current and historical control regime exercised by the Courts of Accounts at the constitutional level, to identify the contours of their action, subsequently shaped by specialized infra-constitutional and infralegal legislation